KEPEMIMPINAN IMAM DALAM GEREJA SINODAL: DARI OTORITAS MENUJU PERSEKUTUAN PARTISIPATIF - ambros ratu; Fransiskus Djo (STP St. Bonaventura Medan, 2025)
This article examines, from a pastoral perspective, the transformation of priestly leadership in the Catholic Church from a pastor-centered model to a form of leadership that actively involves all the faithful. The synodal movement, reaffirmed by Pope Francis, positions the Church as the People of God journeying together in listening to the Holy Spirit and discerning God’s will. Within this framework, priestly leadership is no longer understood as a structure of control or a locus of unilateral decision-making, but rather as a ministry characterized by dialogue, collaboration, and participation. Drawing on ecclesial documents such as Lumen Gentium, Presbyterorum Ordinis, Pastores Dabo Vobis, Evangelii Gaudium, and the Code of Canon Law, this article argues that the identity of the priest as cooperator ordinis episcoporum demands the capacity to unite the faithful, to build spaces for communal discernment, and to empower the charisms of the baptized within the life of the Church. This study affirms that in a synodal Church, priests are called to be shepherds who listen, cultivate spiritual dialogue, and lead the community collaboratively toward its evangelizing mission. Consequently, priestly leadership develops from a centralistic pattern into a form that strengthens the participation of the entire People of God, enabling the Church to remain faithful to its synodal nature as a community of communion and mission.